Pengaruh Partisipasi Anggaran, Komitmen Organisasi, Gaya Kepemimpinan Transformasional, Asimetri Informasi pada Budgetary Slack Hotel Berbintang - Palupi, Devia Galuh; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi, 2020)
The purpose of this study was to obtain empirical evidence about the effect of budgetary participation, organizational commitment, transformational leadership style, and information asymmetry on budgetary slack in the 5-Star Hotel in the Nusa Dua Region. The population used was as many as 18 5-star hotels in the Nusa Dua area with a sample of 73 lower and middle level managers using purposive sampling methods and data analysis techniques used were multiple linear regression. Based on the results of this study, it was found that budgetary participation and information asymmetry had a positive effect on budgetary slack, while organizational commitment and transformational leadership style negatively affected budgetary slack in the 5-Star Hotel in the Nusa Dua Region. Keywords: Participation; Commitment; Transformational; Asymmetry; Slack.